Mein Kampf - Hitler, Adolf 1889-1945; Translated by Manheim, Ralph (London Hutchinson and Co Ltd., 1969)
Contains a new introduction of D.C.Watt, Professor of International History at the University of London, which analyses Hitler's background, gives the origins and history for the book, and ends with a critical assessment both of Hitler's incoherent ideas and his ruthless understanding of political power.
Include Index
Keywords: Germany -- Politics and government -- Nationalsozialistische Deutsche Arbeiter-Partei